Islamic Law in Plural Legal Systems and the SDGs: A Comparative Analysis of Indonesia, Bangladesh, and Kenya - Alwy Ahmed Mohamed; Md. Riazul Haque; Alaa Alkhateeb (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze how Islamic law is interpreted, institutionalized, and practiced in the fields of family, inheritance, and Islamic finance, as well as how these interpretations interact with national constitutions and international human rights norms. Theoretical framework: The theoretical framework of this research is based on the concept of legal pluralism, the relationship between religious law and state law, and the framework of the Sustainable Development Goals (SDGs), specifically SDG 5 (Gender Equality), SDG 10 (Reducing Inequality), and SDG 16 (Peace, Justice, and Strong Institutions). Literature review: Reviews the theory of legal pluralism, constitutional debates in multireligious postcolonial countries, and previous studies of Islamic legal practice in Indonesia, Bangladesh, and Kenya, with a focus on issues of gender, judicial consistency, and human rights. Methods: This study uses a comparative qualitative method with a doctrinal legal analysis approach, legal case evaluation, and secondary literature synthesis. Data were analyzed across jurisdictions to compare Islamic legal practices in Indonesia, Bangladesh, and Kenya. Results: The results show different models of Islamic law implementation: Indonesia combines national and regional authorities (e.g., in Aceh), Bangladesh enforces Islamic family law through civil courts, while Kenya restricts sharia to the constitutionally recognized Kadhi courts. Legal pluralism promotes cultural inclusion, but it also creates inconsistencies in the protection of gender rights and the coherence of the justice system. Implications: Affirms the importance of harmonizing religious law with the constitution to strengthen human rights, inclusive justice, and legal reform by the SDGs. Novelty: A comparative analysis of three countries with different contexts and the direct link of Islamic law to the global agenda of the SDGs, in particular, gender equality, inequality reduction, and institutional strengthening.